2021
DOI: 10.1101/2021.03.30.437506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human brain organoids assemble functionally integrated bilateral optic vesicles

Abstract: During embryogenesis, optic vesicles develop from the diencephalon via a complex process of organogenesis. Using iPSC-derived human brain organoids, we attempted to simplify the complexities and demonstrate the formation of forebrain-associated bilateral optic vesicles, cellular diversity, and functionality. Around day thirty, brain organoids could assemble optic vesicles, which progressively develop as visible structures within sixty days. These optic vesicle-containing brain organoids (OVB-Organoids) constit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 94 publications
1
14
0
Order By: Relevance
“…This environment and the time frame is similar to when IBA1 + -cells have been reported to appear in human embryonic development (Bloom and Bartelmez, 1940; Kelemen and Jánossa, 1980; Monier et al, 2007; Rezaie et al, 2005). Our results also support a recent study that identified a cluster of microglial cells using RNA-sequencing of brain organoids with bilateral optic vesicles (Gabriel et al, 2021). However, in contrast to human retinal development (Hu et al, 2019), we rarely observed microglia-like cells in the retinal cup at 5 weeks or later ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This environment and the time frame is similar to when IBA1 + -cells have been reported to appear in human embryonic development (Bloom and Bartelmez, 1940; Kelemen and Jánossa, 1980; Monier et al, 2007; Rezaie et al, 2005). Our results also support a recent study that identified a cluster of microglial cells using RNA-sequencing of brain organoids with bilateral optic vesicles (Gabriel et al, 2021). However, in contrast to human retinal development (Hu et al, 2019), we rarely observed microglia-like cells in the retinal cup at 5 weeks or later ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The data regarding intrinsic microglia occurrence are controversial. Whereas single-cell RNA-sequencing of brain organoids with bilateral optic vesicles identified a glial cluster expressing microglia-specific markers (Gabriel et al, 2021), other studies do not report, or the provided data do not support, their presence in retinal organoids (Collin et al, 2019; Cowan et al, 2020; Kim et al, 2019). A microglial transcriptional signature can be detected in human embryonic retinal tissue by gestational week 5 (Hu et al, 2019; Mellough et al, 2019) suggesting that microglia appear early in development.…”
Section: Introductionmentioning
confidence: 96%
“…As the decisive factor between NR and RPE is VSX2, it is widely accepted as an indicator of cells with NR identity in ROs as well. 9,35,[37][38][39][40]46 RPE fate is co-controlled by another TF (MITF) that it is expressed throughout the entire structure in the early optic vesicle. Later on, it is restricted to the RPE.…”
Section: Recapitulating Retina Development In Vitromentioning
confidence: 99%
“…2017 ). Very recently, optic vesicle-containing brain organoids (OVB) have been grown ( Gabriel et al. 2021 ).…”
Section: Physiology Of Cerebral Organoidsmentioning
confidence: 99%
“…Importantly, they are light-sensitive, and ‘various light intensities could trigger photosensitive activity of OVB-organoids (...). Thus, brain organoids have the intrinsic ability to self-organize forebrain-associated primitive sensory structures in a topographically restricted manner’ ( Gabriel et al. 2021 ).…”
Section: Physiology Of Cerebral Organoidsmentioning
confidence: 99%